Economic values of conservation and management attributes in Bako National Park, Sarawak, Malaysia - Kamri, Thalany (2014)
Existing for 55 years to date, the key attributes of Bako NP are seen to be under threat. These deficiencies are due to low levels of finance for its conservation and management purposes. An ideal national park should have its objective of generating enough income to cover its operating expenses and a surplus to invest in both conservation and management. The policy options to increase park revenue would remain unclear with lack of information on demand parameters. This study illustrates the estimation of economic values of national park attributes. The techniques applied for the estimation of use value in national parks are contingent valuation method and choice experiment. A total of 564 respondents were randomly selected amongst foreign and local visitors at Bako NP. The CVM elicits visitors’ willingness to pay for the improvement of conservation and management in the park. The logit model is defined according to dichotomous choice method to obtain the willingness to pay for the proposed entrance fee bid. A total of 80.5% of the respondents among foreign visitors agreed to contribute for national park conservation. However, only 43% of the respondents among local visitors are willing to contribute for the same purpose. Foreign visitors are willing to pay 1.58 times higher than the current entrance fee. Their willingness to pay is RM51.76. On the other hand, local visitors have a slight increase in their willingness to pay as compare to their current charges which is only RM18.80. In CE, two blocks of estimation were analysed that are conservation and management. For conservation, a total of 70.5% of respondents selected one of the options above the status quo level of conservation fee. The results show that visitors are mostly concern for the issue of decreasing in the population of rare species. Visitors are willing to pay to improve the level from continuous to slow down the decreasing rate. For the case of management, a total of 64.3% of the respondents selected one of the options above the current situation of entrance fee. The results show that visitors are most concern for protection level of the park. Visitors are willing to pay to improve the level from moderate to high level of protection. The consumer surplus is estimated to be approximately RM31.76 for foreign visitors and RM8.80 for local visitors, representing the extra benefits that visitors gain from the park. The value of Bako NP is calculated by multiplying the number of foreign (32344) and local visitors (13112) by the willingness to pay for visiting Bako NP. The result shows that the estimated total economic value of Bako NP for 2013 is RM1.9 million.